1972
DOI: 10.1172/jci106918
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of human platelets

Abstract: A B S T R A C T Human platelets were separated by density-centrifugation into heavy and light populations. Heavy platelets have an average volume approximately twofold greater than light platelets, and have previously been shown to be young platelets.All 11 enzymes of the Embden-Meyerhof pathway plus the five related enzymes: phosphoglucomutase, glucose-6-P dehydrogenase, 6-P-gluconic dehydrogenase, a-glycerol-P dehydrogenase, and glutathione reductase (TPNH) were examined in cell lysates from total, heavy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

1977
1977
1990
1990

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(14 citation statements)
references
References 31 publications
3
11
0
Order By: Relevance
“…These values are essentially identical with those reported by Karpatkin (18) but one-half to two-thirds of those reported by others (19,20 (Fig. 3) while the small amount of glucose-'C converted to C02 increased exponentially.…”
Section: Methodssupporting
confidence: 91%
“…These values are essentially identical with those reported by Karpatkin (18) but one-half to two-thirds of those reported by others (19,20 (Fig. 3) while the small amount of glucose-'C converted to C02 increased exponentially.…”
Section: Methodssupporting
confidence: 91%
“…It is possible that the platelets entering the circulation from blood de pots to compensate for the aggregated and destroyed ones were not as active hemostatically. It has been shown that in normal subjects circulating platelets display heterogeneity o f size, density and metabolic function with larger ones showing greater metabolic activity (14,19). Weston et al (45) have shown that, after charcoal hemoperfusion in patients with fulminant hepatic failure, mean median volume o f platelets decreased and capillary bleeding time was doubled despite the limited drop in arterial platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, the five patients with capillary bleeding times over 30 minutes but platelet counts above 100 x 109/1 would seem to have a considerable degree of platelet dysfunction. In normal subjects circulating platelets display heterogeneity of size, density, and metabolic function with the larger ones i-L. showing greater metabolic activity (Karpatkin and Charmatz,, 1969;Ginsburg and Aster, 1972). If these larger platelets are haemostatically the most active, then their selective deficiency in fulminant hepatic failure could explain the low platelet volumes found and the long capillary bleeding times.…”
Section: Detection Of Platelet Aggregatesmentioning
confidence: 99%